Analysis of Irrigation Network and Operational Real Needs (AKNOP) at Cirongkob Dam - Prosidiawan, Avan; Tohana, Tohana; Santika, Rifki Adhy; Tribhuwana, Awliya (Devotion : Journal of Research and Community Service, 2025)
Irrigation network maintenance plays a strategic role in ensuring efficient and sustainable water distribution to support agricultural productivity. This research aims to analyze the condition of the irrigation network and calculate the Actual Operation and Maintenance Needs (AKNOP) at the Cirongkob Weir in Kuningan Regency, West Java. The research method uses a quantitative and qualitative approach through field observations, water discharge measurements, evaluation of irrigation channels and structures, and calculation of maintenance costs based on the technical guidelines of the Ministry of Public Works and Housing (PUPR). The analysis results show that the irrigation channels are generally functional, although light to moderate damage was found that affects water distribution efficiency. AKNOP calculations indicate that most of the budget is allocated to rehabilitation and contractual maintenance activities. Efforts to improve irrigation efficiency should focus on optimizing routine maintenance, strengthening farmers’ institutions (P3A), and implementing water discharge monitoring. Through these strategies, the sustainability of the irrigation system and food security in the Cirongkob area can be maintained. The implications of this research provide empirical foundations for evidence-based irrigation management policies, contribute to the development of standardized AKNOP calculation methodologies for similar irrigation systems across Indonesia, and offer practical guidelines for optimizing budget allocation in irrigation infrastructure maintenance.